Extracurricular Activities and Academic Performance of Student Leaders at Asia-Pacific International University - Choi, Seung Yeon; Sattayawaksakoon, Damrong (12th International Scholars Conference 2025, 2026)
This study examines the impact of leadership experience in extracurricular activities and time management skills on the academic performance of students at Asia-Pacific International University (AIU). Using a quantitative approach, data were collected via a Google Form survey from 80 students holding leadership positions such as club officers, department officers, and student council officers. The study employed descriptive statistics and regression analysis to explore the relationships between leadership experience in extracurricular activities, time management skills, and academic performance. Findings reveal that leadership experience in extracurricular activities positively influences academic performance, as measured by GPA, while time management skills did not show a significant effect. The study highlights the importance of balanced extracurricular involvement and effective leadership training for fostering academic success. Recommendations include promoting leadership development programs, mentorship initiatives, and improved time management strategies. Limitations and directions for future research are also discussed.